Student Engagement Siswa Kebutuhan Khusus: Studi Komparatif Karakteristik Hambatan Belajar Pada Sekolah Inklusi Di SMP Negeri 22 Semarang - Yahya, Nasywa Aqila Fadhilla; Sigit Hariyadi (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2026)
Inclusive education in Indonesia continues to develop as an effort to create an equal and non-discriminatory learning environment. However, the reality on the ground shows significant gaps in access and serious barriers to student engagement for students with special needs, such as deaf, mentally retarded, and slow learners . This study aims to map the characteristics of learning barriers and analyze student engagement patterns at SMP Negeri 22 Semarang. A qualitative approach with a case study design was used to explore this phenomenon through participant observation and in-depth interviews. The results showed unique differences in behavioral, cognitive, and emotional patterns among these student groups. Furthermore, it was found that a personalized direct instruction approach and strong support from teachers and parents are key to maintaining student motivation and resilience in the school environment. These findings emphasize that precise, accommodating learning strategies tailored to the variety of individual barriers are crucial for the effective implementation of inclusive education in the future.